IMPACT OF INTEGRATED NUTRIENT MANAGEMENT ON YIELD, NUTRIENT UPTAKE, PROTEIN CONTENT OF WHEAT (TRITICUM ASTIVAM) AND SOIL FERTILITY IN A TYPIC HAPLUSTERT - G. D. SHARMA; THAKUR, RISIKESH; SOM RAJ; D. L. KAURAW; P. S. KULHARE (The Bioscan, 2013)
The present investigation were conducted for two rabi seasons during 2007 and 2008 in the field of Department of Soil Science and Agricultural Chemistry, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh to study the effect of integrated nutrient management on yield, nutrient uptake, protein content and soil fertility of wheat in a Vertisol. The results revealed that the substitution of 25% NPK through farmyard manure in recommended dose of NPK along with 5 kg Zn/ha and PSB + Azotobactor recorded significantly higher grain yield (58.23 q/ha) over the 100% NPK treatment (49.79 q/ha). However, the maximum nutrient (N, P, K, S and Zn) uptake by wheat 147.08, 28.44, 174.6, 51.94 kg /ha and 335.6 g/ ha, respectively were observed in the treatment receiving 75% NPK + 5t FYM ha-1 + PSB+Azotobactor + Zn (T9). Further, the conjunctive use of inorganic fertilizers and organic manure along with biofertilizers and micronutrients gave highest available N, P, K, S and Zn in soil as compared to other treatment combinations. Thus, integrated resource management improved the crop yields, produces quality grain as well as improved the soil fertility